Do gamblers invest in lottery stocks? - Emily Kormanyos; Tobin Hanspal; Andreas Hackethal (Leibniz Institute for Financial Research SAFE, 2023)
Previous studies document a relationship between gambling at the aggregate level and investments in securities with lottery-like features. We combine data on individual gambling consumption with portfolio holdings and trading records to examine whether gambling and trading act as substitutes or complements. We find that gamblers are more likely than average to hold lottery stocks, but less likely than active traders. Our results suggest that gambling behavior across domains is less relevant than other characteristics that predict investing in high-risk and high-skew securities, and gambling on and off the stock market act as substitutes to satisfy the same need, e.g., sensation seeking.
Keywords: G50; G40; D14; G11; G15; 330; Gambling; Retail investors; Lottery stocks